Análise in silico de um novo composto possível inibidor de ciclooxigenase 2 utilizando docking molecular - Pedroso, Sofia Dallasta (Universidade Federal de São Carlos, 2021)
This work describes the study of the formation of complexes between the enzyme cyclooxygenase (COX-2) and some of its inhibitors. For this purpose, the known inhibitors celecoxib (CEL), rofecoxib (RCX) and Korean 21 and the ligand RJA4, a potential inhibitor, were evaluated in the studies. The activity of COX-2 can be blocked by non-steroidal anti-inflammatory drugs (NSAIDs) such as CEL, RCX, among others. These drugs are known for their action in reducing inflammatory reactions, pain and fever, as well as their anticoagulatory effect when used in low doses, however, the first side effects detected were kidney failure, and peptic ulcer. The work was carried out using molecular docking simulations evaluating the possible capacity for selective COX-2 inhibition by the RJA4 compound, whose structure is similar to that of other COX-2 inhibiting drugs, generically known as coxibs. For the docking work, the protein with PDB code 5IKR, a crystallographic complex formed by the human COX-2 enzyme and the inhibitor mefenamic acid (ID8), was used. Docking studies were done using the same enzyme cavity occupied by mefenamic acid to position the studied compounds. The evaluation of the docking results was done by graphic analysis, first selecting poses (position, orientation and conformation) of the compounds at the site, and then the interactions between atoms of the ligands and that of the protein amino acids were evaluated: hydrogen bonds, van der Waals interactions and π interactions. It was observed that the π interaction of the ligands with Val523 deserves to be highlighted, a residue related to the specificity for COX-2. To obtain more details on this interaction computational calculations based on electronic density were also performed. The results indicate that the RJA4 compound is positioned similarly to the studied molecules (coxibs, Korean 21, ID8) making similar interactions with the COX-2 enzyme, which suggests that this compound may be a good inhibitor of COX-2. This is the starting point for further studies, whether theoretical, such as molecular dynamics, or in vitro, to experimentally determine the inhibitory potential of the studied molecule.
In silico analysis of a new composite as a possible cycloxygenase 2 inhibitor using molecular docking
Keywords: Ciclooxigenase 2; Docking; Desenho de compostos baseado em estrutura; CIENCIAS BIOLOGICAS::BIOQUIMICA::QUIMICA DE MACROMOLECULAS